2021
DOI: 10.1186/s13287-021-02595-0
|View full text |Cite
|
Sign up to set email alerts
|

CAR-T cell therapy in T-cell malignancies: Is success a low-hanging fruit?

Abstract: Chimeric antigen receptor T-cell (CAR-T) therapy has been prosperous in the treatment of patients with various types of relapsed/refractory (R/R) B-cell malignancies including diffuse large B-cell lymphoma (DLBCL), B-cell acute lymphoblastic leukemia (B-ALL), follicular lymphoma (FL), mantle cell lymphoma (MCL), and multiple myeloma (MM). However, this type of therapy has faced serious hindrances in combating T-cell neoplasms. R/R T-cell malignancies are generally associated with poor clinical outcomes, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 137 publications
(300 reference statements)
0
47
0
Order By: Relevance
“…Use of allogeneic donor cells would also eliminate the risk of contamination of the CAR product with tumor cells. In addition, NK cells are short-lived, so they would not persist in the host and would not cause long-term T-cell aplasia when targeting T-cell lineage molecules [15].…”
Section: Discussionmentioning
confidence: 99%
“…Use of allogeneic donor cells would also eliminate the risk of contamination of the CAR product with tumor cells. In addition, NK cells are short-lived, so they would not persist in the host and would not cause long-term T-cell aplasia when targeting T-cell lineage molecules [15].…”
Section: Discussionmentioning
confidence: 99%
“…Among the transforming growth factor-b is a predominantly immunosuppressive soluble factor identified in the TME. T-cell differentiation into Tregs is triggered by this powerful cytokine as well as the immunosuppressive polarisation of macrophages phenotype M2 [48]. The development of a chimeric antigen receptor that responds to transforming growth factor-b showed that chimeric antigen receptors usage to identify a soluble feature and T-cells are rearranged to transform inhibitory signals into antitumor activity signals [49].…”
Section: Switching From An Inhibited To a Stimulatory Mode Of Receptorsmentioning
confidence: 99%
“…Cancer immunotherapy first started as an idea to employ the patients' immune system and its components as fighting tools against various types of neoplasms (10,11). Today, monoclonal antibody (mAb)-based therapies, cancer vaccines, adoptive cell therapy (ACT), and oncolytic viruses are among famous types of cancer immunotherapy that have gained preclinical and clinical success (10).…”
Section: Introductionmentioning
confidence: 99%
“…The theory of utilizing T cells as fighting tools for a selective fight against cancer, which started in the early 1990s, has now become a treatment option for certain patients with B-cell-based malignancies (12)(13)(14)(15)(16)(17)(18)(19)(20). Over the past few years, the field of CAR-T therapy has progressed remarkably (11,21). In particular, various CAR generations have been developed and many innovative strategies have been proposed, aimed at improving the safety and efficacy of CAR-T therapy (11,(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation